Comparison between vertical jumps of high performance athletes on the Brazilian men's beach volleyball team - Ricarte Batista, G.; Freire De Araujo, R.; Oliveira Guerra, R. (The Journal of Sports Medicine and Physical Fitness, 2008)
Aim: The aim of this paper was to compare the anthropometric profile and the vertical jumps of two groups of Brazilian male high performance beach volleyball players. Methods: The sample consisted of 38 male beach volleyball players from the Brazilian Beach Volleyball Circuit of 2006, allocated to two groups according to national ranking of their teams. Anthropometric measures and performance in vertical jumps were assessed using a specific methodology. Results: The anthropometric results of the groups showed no statistically significant differences. The players of group 1 (G1) were better in the spike jump (P<0.01), block jump (P<0.01) and block difference (P<0.01) than the players of group 2 (G2). The prediction model of the spike jump for G2 included body mass and standing spike reach (adjusted R2=0.77) while for the block jump model it was body mass and standing block reach (adjusted R2=0.73). The regression models for G1 were not statistically significant. Conclusion: It is likely that vertical jump height (spike and block) influences the performance of beach volleyball players, and consequently the performance of their teams, since the present study found higher values in G1 than in G2 for the spike jump, block jump and block difference. However, an athlete's success is not related only to the variables investigated in this study; technical skill, tactics, psychology and physical conditioning can also play a role.